PERFORMANCE EVALUATION OF VERI-Q RED HAEMOGLOBIN METER FOR POINT-OF-CARE HAEMOGLOBIN AND PACKED CELL VOLUME ESTIMATIONS - Apollos Vivian; Jacob Ranson; Jeremiah Zaccheaus (Sanamed, 2024)
Introduction: Haemoglobin (Hb) and packed cell volume (PCV) are tests used in the assessment of anaemia. The Veri-Q haemoglobin meter is a new device in the point-of-care market used for the quantitative measurement of haemoglobin and packed cell volume. This study aimed to evaluate the performance of the Veri-Q haemoglobin meter for the assessment of haemoglobin and packed cell volume.